A Study on Fuzzy TÎ“-Ideals in Ternary Î“-Semiring - Revathi, K; Madhusudhana Rao, D; Sundarayya, P; Satish, T (International Journal of Engineering and Technology, 2018)
The concepts of fuzzy theory in TÎ“-semiring in terms of fuzzy TÎ“-ideals in TÎ“-semirings are introduced and also we made a study on some properties of fuzzy TÎ“-Ideals in TÎ“-semiring.Â Â